2019
DOI: 10.1111/ijcp.13403
|View full text |Cite
|
Sign up to set email alerts
|

The Multidimensional Prognostic Index in general practice: One‐year follow‐up study

Abstract: Background Older patients’ health problems in general practice (GP) can often not be assigned to a specific disease, requiring a paradigm shift to goal‐oriented, personalised care for clinical decision making. Purpose To investigate the predictive value of the comprehensive geriatric assessment (CGA)‐based Multidimensional Prognostic Index (MPI) in a GP setting with respect to the main healthcare indicators during the 12 months following initial evaluation. Methods One hundred twenty‐five consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…A metanalysis of 29 randomized controlled trials conducted in over 14,000 older patients have shown that the CGA is highly effective in improving diagnosis and management [ 28 ]. Recent studies employing CGA-based innovative, feasible tools for the assessment of multidimensional, individualized prognosis clearly showed that the latter disclose critical factors for trajectories which go beyond organ-center medicine and chronological age [ 29 31 ] and apply also during the ongoing pandemic [ 11 , 23 ]. Of note, in our analysis the Braden scale but not the Conley scale—which addresses physical factors only—reached and surpassed the predictive power of the P/F or of the LDH levels, supporting the knowledge that functions escaping diagnostics in usual care influence the ability to thrive in advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…A metanalysis of 29 randomized controlled trials conducted in over 14,000 older patients have shown that the CGA is highly effective in improving diagnosis and management [ 28 ]. Recent studies employing CGA-based innovative, feasible tools for the assessment of multidimensional, individualized prognosis clearly showed that the latter disclose critical factors for trajectories which go beyond organ-center medicine and chronological age [ 29 31 ] and apply also during the ongoing pandemic [ 11 , 23 ]. Of note, in our analysis the Braden scale but not the Conley scale—which addresses physical factors only—reached and surpassed the predictive power of the P/F or of the LDH levels, supporting the knowledge that functions escaping diagnostics in usual care influence the ability to thrive in advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…A higher MPI-score is associated with increased 1-year mortality, hospitalization or admission to a healthcare institution. [15][16][17][18][19][20] The MPI, which was originally developed to predict mortality, has also been suggested as a frailty assessment model. 21,22 However, whether the MPI-score reflect the degree of frailty has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…hearth failure, 7 chronic kidney disease, 8 cancer, 9 dementia, 10 neuropsychological disorders 11 and diabetes mellitus, 12 and in several settings such as in hospitalized patients, 4,27 in the community-dwelling subjects who underwent a CGA to be admitted to nursing homes or homecare services, 5 as well as at population level 28 and at the ambulatory of the General Practitioner. 29 A previous study has already showed the strong association and validity between the SELFY-MPI and the MPI. 13 This study explores the feasibility of the SELFY-MPI in people of different ages and from different countries.…”
Section: Discussionmentioning
confidence: 93%